UPAYA PENINGKATAN PENERAPAN SANITASI PADA INDUSTRI PANGAN SKALA KECIL - Lya Agustina (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2018)
Food security can be realized by applying the principles of sanitation in an industry. In this case, the SSOP (Sanitation Standard Operating Procedures) becomes a mandatory sanitation program for an industry to improve the quality of products and ensure a system of food production security. This research was carried out in three small-scale food industries (tofu, crackers and bread). Primary and secondary data obtained will be analyzed based on 8 key aspects of SSOP. Based on the key to implementing SSOP, basically the implementation of sanitation really needs to be improved, especially in terms of preventing cross contamination and eliminating pests. Efforts to implement hygiene workers are focused on the basic things, the using of gloves, masks and head covering (prevention of cross contamination), while the application of overall environmental sanitation by way of routine socialization directly or indirectly (through sanitation symbols attached to the area production) by industrial management.